Intelligent Information System for Monitoring the Quality of Drinking Water - Gidayatzada, Sayyara; Abdullayeva, Gulchin (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
The article explores the global issue of water scarcity. Methods are being applied to eliminate water pollution, which can lead to water shortages. Azerbaijan is also one of the countries suffering from this problem. A global approach to the issue is required. Considering the complexity of the problem, a prototype is being developed, and potential solutions are demonstrated on it. The JWR is taken as the prototype object. The conceptual model, functional model, and system architecture have been presented.